ICT-Based Teaching of English at Madrasah Aliyah in Kalimantan - Fauzan, Umar; Pimada, Luluk Humairo (TARBIYA: Journal of Education in Muslim Society, 2018)
AbstractSome teachers use ICT as a medium for teaching by using slide presentations. Many others use Information and communication technology (ICT)  as a teaching media to develop the students’ independent learning. The purpose of this research is to reveal: what ICT applied in teaching English in Kalimantan, how to apply ICT in teaching English in Kalimantan, and what barriers factor in developing language skills through ICT utilization in Kalimantan. This is a qualitative descriptive study that attempts to describe the use of ICT in English teaching in Kalimantan. The subjects of this study are English teachers in three provinces in Kalimantan; East Kalimantan, South Kalimantan, and North Kalimantan. Some instruments were used, including: interviews, observation, and documentation. Miles and Hubberman models are used for data analysis. The results show that: first, the English teachers use ICT in English classes in Kalimantan although it is very limited, since they are only familiar to use multimedia. Meanwhile, E-Media, E-Learning, E-Library, and Web-based Communities are rarely used. Secondly, the teachers of madrasah Aliyah in English teaching in Kalimantan more often use LCD projector by using a song or film in the laptop. Third, some obstacles in the application of ICT in teaching English are the ICT equipment problem, limited internet access, lack of the utilization of applications in cellphones, and age constraints.AbstrakBeberapa guru menggunakan Teknologi informasi dan komunikasi (TIK)sebagai media untuk mengajar dengan menggunakan slide presentasi. Banyak orang lain menggunakan TIK sebagai media pengajaran untuk mengembangkan pembelajaran mandiri siswa. Tujuan dari penelitian ini adalah untuk mengungkapkan: apa TIK yang diterapkan dalam pengajaran bahasa Inggris di Kalimantan, bagaimana menerapkan TIK dalam mengajar bahasa Inggris di Kalimantan, dan apa faktor penghambat dalam mengembangkan keterampilan bahasa melalui pemanfaatan TIK di Kalimantan. Ini adalah studi deskriptif kualitatif yang mencoba menggambarkan penggunaan TIK dalam pengajaran bahasa Inggris di Kalimantan. Subjek penelitian ini adalah guru bahasa Inggris di tiga provinsi di Kalimantan; Kalimantan Timur, Kalimantan Selatan, dan Kalimantan Utara. Beberapa instrumen digunakan, termasuk: wawancara, observasi, dan dokumentasi. Model Miles dan Hubberman digunakan untuk analisis data. Hasilnya menunjukkan bahwa: pertama, guru bahasa Inggris menggunakan TIK di kelas bahasa Inggris di Kalimantan meskipun sangat terbatas, karena mereka hanya terbiasa menggunakan multimedia. Sementara itu, E-Media, E-Learning, E-Library, dan Komunitas berbasis web jarang digunakan. Kedua, para guru madrasah Aliyah dalam pengajaran bahasa Inggris di Kalimantan lebih sering menggunakan proyektor LCD dengan menggunakan lagu atau film di laptop. Ketiga, beberapa kendala dalam penerapan TIK dalam pengajaran bahasa Inggris adalah masalah peralatan TIK, akses internet yang terbatas, kurangnya pemanfaatan aplikasi dalam ponsel, dan batasan usia. How to Cite : Fauzan, U., Pimada, L. H. (2018).  ICT-Based Teaching of English at Madrasah Aliyah in Kalimantan. TARBIYA: Journal of Education in Muslim Society, 5(2), 193-211. doi:10.15408/tjems.v5i2.10414.